Mitral valve reconstruction – timing, surgical techniques and results (Swiss Medical Weekly, 2012)
Mitral valve insufficiency is the second most common heart valve disease and untreated regurgitation leads to enlargement of the left atrium, atrial fibrillation and heart failure. Besides functional regurgitation, the main cause is degenerative valve disease with elongation of the chordae tendineae and prolapsing of the leaflets. Surgical repair is the gold standard therapy for mitral valve insufficiency today. Numerous techniques have been described. Proposed techniques are resection of the prolapsed segment, chordae transfer and ring annuloplasty. Lately, the implantation of neochordae and the loop-technique has been established and is the preferred technique in many centres. There is ongoing discussion about the ideal timing for the intervention in asymptomatic patients. Some groups prefer a watchful waiting strategy; others promote an early intervention, which is also recommended in the guidelines. Results of surgical mitral valve repair are good with low rates of re-intervention and mortality. With minimally invasive techniques, the patient satisfaction is high and hospital stay is short. In conclusion, mitral valve repair should be the preferred strategy in patients with symptomatic mitral valve insufficiency or with asymptomatic mitral valve insufficiency in accordance with the guidelines. Modern repair techniques such as neo-chord implantation with the loop-technique combined with minimally invasive access routes result in low mortality and morbidity and short hospital stay as well as high patient satisfaction.